Asset Price Bubbles and Monetary Policy: Why Central Banks Have Been Wrong and What Should Be Done - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2008)
Over the last several years debate over monetary policy has focused on two issues, inflation targeting and asset price bubbles. This paper explores the case for explicitly targeting asset price bubbles, a policy that the Federal Reserve Bank has opposed on the grounds that it is both infeasible and undesirable. The paper argues that the Fed is wrong on both counts. Asset price bubbles are identifiable. Bubbles also do significant economic harm through the debt footprint effects they leave behind and through interest rate blunderbuss effects resulting from attempts to mitigate the aggregate demand impact of bubbles. Managing bubbles calls for additional policy instruments. These can be provided a system of asset based reserve requirements (ABRR).
urn:nbn:de:101:1-20080818143
Keywords: 330; Spekulationsblase; Geldpolitik; Antizyklisches Verhalten; Basler Akkord; Theorie; EU-Staaten